(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Quality assurance (QA) is essential in healthcare to ensure accurate diagnoses, effective treatments, and patient safety. This article examines the roles of lab technicians and nurses in maintaining QA standards within the healthcare ecosystem. Lab technicians are responsible for proper sample handling, accurate testing procedures, data analysis, documentation, and continuous improvement in laboratory testing. Nurses contribute to QA through patient assessment, medication administration safety, infection control practices, patient education, and collaborative care coordination.